Remote Control of Food Storage Parameters Based on the Database - Oqilov Azizbek; Oripov Shoxruxmirzo; Eshonxodjayev Hokimjon Xotamjon o’g’li; Sobirov Anvarjon Sobirov (Zien Journals, 2022)
At present, human resources are one of the most fundamental factors in human need for food in an ever increasing period of time. And one of the best ways to do this, of course, is associated with the restoration of modern food establishments
Keywords: Discussions; organization; storage; remote control